PENGARUH KONSENTRASI ETANOL TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN SIRIH MERAH (Piper crocatum Ruitz & Pav) MENGGUNAKAN METODE MICROWAVE ASSISTED EXTRACTION (MAE) - Yasa, I Gede Tirta; Putra, Nengah Kencana; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i03.p06, 2019)
This study was conducted to determine the effect of ethanol concentration on antioxidant activity and to obtain the highest antioxidant activity in red betel leaves extract using the MAE method. The experimental design used in this study was a completely randomized design (CRD) with an ethanol concentration treatment consisting of five levels, namely 50%, 60%, 70%, 80%, and 90%. All treatments were repeated three times to obtain 15 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan test. Treatment of ethanol concentration had a very significant effect (P <0.01) on yield, total phenol, total flavonoids, and antioxidant activity. The results showed that 90% ethanol concentration was the best treatment which produced a yield of 25.17%, total phenol 106.00 mg GAE / g extract, total flavonoids 46.98 mg QE / g and antioxidant activity based on IC50 at 81.61 ppm. Keywords : red betel leaves, ethanol, MAE, antioxidant activity.